Inefficacy or Paradoxical Effect? Uveitis in Ankylosing Spondylitis Treated with Etanercept - Bernd Raffeiner; Francesca Ometto; Livio Bernardi; Costantino Botsios; Leonardo Punzi (Case Reports in Medicine)
Ankylosing spondylitis (AS) is presented with axial and peripheral articular involvement. Uveitis is a severe and rather specific manifestation of AS. Biologics targeting tumor necrosis factor (TNF) α are effective on both articular and ocular manifestations of disease. The occurrence of uveitis in patients that never had eye involvement or the relapse of uveitis is described during anti-TNFα treatment. The frequency of these events is slightly higher during therapy with etanercept. The available TNFα blockers show different pharmacokinetics and pharmacodynamics yielding different biological effects. There is an ongoing debate whether uveitis during anti-TNFα has to be considered as paradoxical effect or an inadequate response to therapy. Here, we present a case report and review what the evidences for the two hypotheses are.